Ekstrak Lidah Mertua (Sansevieria sp.) Efektif dalam Mereduksi Volatile Organic Compound (VOC)-Benzena Dalam Ruang - Kahar Kahar; Mimin Karmini; Ade Kamaludin (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
Extract of Snake Plant (Sansevieria sp.) As a Reducer of Indoor Air Pollution, Volatile Organic Compounds (VOC) -Benzene. The quality of the indoor environment has become a health concern, as city dwellers spend 80-90% of their time indoors, where outdoor air pollution is several times higher. Indoor potted plants can remove airborne contaminants such as volatile organic compounds (VOCs), more than 300 of which have been identified in indoor air. and a very wide range of light, and is resistant to pollutants. This plant is also able to absorb more than 107 harmful pollutants in the air, this is due to Sansevieria sp. contains the active ingredient Pregnane glycosides. These active ingredients function to reduce pollutants into organic acids, sugars and amino acids so that these pollutants are no longer harmful to humans3. This study aims to see the extract of the tongue-in-law in reducing Volatile Organic Compounds (VOCs) in the room. The method used in this research is true experimental design with pre and post-test design without control design. Based on the results of the study, the decrease in benzene levels was done by using the sansevieria extract concentration with the average reduction proportions, namely: 10 ppm concentration; 98.24%, 20 ppm; 98.47%; 30 ppm; 98.73%. The results of statistical tests using the Mann Whitney U test showed that the results were 0.000 <0.05 so that there was a relationship, namely that there was a difference in the concentration of the extract of Sansevieria sp. against decreased levels of benzene. The most effective level of Sansevieria extract in reducing benzene levels in the air was 30 ppm with an average reduction proportion of 98.73%.